Assessment of the implementation of the 'digital classroom' initiative in the Gauteng Provincial Department of Basic Education - Mosehlana, M. B.; Sebola, M. P. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The Gauteng Department of Basic Education (GDBE) is currently one of the departments nationwide that actively engage ICT in the execution of their mandate to ensure that Gauteng has effective schools and learning institutions. As the evolution of the forth industrial revolution is upon our horizon, infusion of ICT in the South Africa schools is essential to provides quality education to Gauteng learners which meets the national standard and can be internationally benchmarked. Universal and convenient access to learning and teaching material for learners contribute to improved standard of education in South Africa. Current debates perceive the education system as being in serious need of improvement. To support the implementation of any e-government initiative, an effective e-government policy and its implementation strategy is key. With special interest on the 3rd Generation of implementation research, policy implementers are required to formulate effective implementation strategies in cognisance of the complex, interconnected and multi-sectoral nature of the implementation process. The 7Cs implementation protocol acknowledges and explains the nature of this complexity and, therefore, provides a framework which guides policy and its concomitant implementation strategy to facilitate achievement of policy goals. This paper seeks to assess the application of the 7Cs protocol in the implementation of the GDBE's "Classrooms of the Future" initiative. The goal is achieved through document analysis (relevant legislative frameworks and official government documents and statements) and heavy reliance on reputable newspaper reports due to lack of published literature on the implementation of this programme as a result of the recent nature of the initiative.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Gauteng Department of Education; E-learning; Digital classroom; 7Cs implementation protocol; Computer-assisted instruction; Communication and technology; Basic education -- South Africa -- Gauteng